2014
DOI: 10.1016/j.jaci.2013.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for live viral and bacterial vaccines in immunodeficient patients and their close contacts

Abstract: The present uncertainty of which live viral or bacterial vaccines may be given to immune deficient patients and the growing neglect of societal adherence to routine immunizations has prompted the Medical Advisory Committee of the Immune Deficiency Foundation to issue recommendations based upon published literature and the collective experience of the committee members. These recommendations address the concern for immunodeficient patients acquiring infections from healthy individuals who have not been immunize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0
42

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(161 citation statements)
references
References 15 publications
0
119
0
42
Order By: Relevance
“…It is known that LAVs stimulate an excellent immune response that is comparable to that induced by infection with the WT pathogen (40). However, LAVs can be less safe than inactivated vaccines, since they can cause disease if inoculated at a high enough dose or in immunocompromised individuals (41). The difference between the dose needed to induce protection and the dose needed to induce disease is defined as the vaccine safety margin.…”
Section: Synonymous Deoptimization Of P1 Results In Attenuation Of Fmmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that LAVs stimulate an excellent immune response that is comparable to that induced by infection with the WT pathogen (40). However, LAVs can be less safe than inactivated vaccines, since they can cause disease if inoculated at a high enough dose or in immunocompromised individuals (41). The difference between the dose needed to induce protection and the dose needed to induce disease is defined as the vaccine safety margin.…”
Section: Synonymous Deoptimization Of P1 Results In Attenuation Of Fmmentioning
confidence: 99%
“…However, studies in vivo showed that the "leaderless virus" was too attenuated and induced only a limited immune response, not sufficient to protect cattle against homologous challenge (11). Interestingly, the leaderless virus behaved like WT virus when it was used like the traditional inactivated FMD vaccine (inactivated antigen in formulation with oil adjuvant), suggesting that the leaderless virus could be an alternative safer option for FMD vaccine production (11,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For children with combined B-and T-cell deficiencies, such as SCID, all live vaccines are contraindicated, and for those with phagocytic disorders live bacterial vaccines are contraindicated. [11] Immunocompetent household contacts of PID patients should not receive smallpox or oral polio vaccine, because these vaccine virus strains may be transmitted to immunocompromised patients. Other vaccines may be administered to close contacts because they pose little risk of transmission to the PID patient.…”
Section: Immunisation Practicementioning
confidence: 99%
“…Other vaccines may be administered to close contacts because they pose little risk of transmission to the PID patient. [11] Antimicrobial prophylaxis Several PIDs may benefit from antimicrobial prophylaxis. In milder antibody conditions, such as IgA deficiency or transient hypogammaglobulinaemia of infancy, recurrent infection may occasionally require short courses of prophylactic antibiotics.…”
Section: Immunisation Practicementioning
confidence: 99%
“…However, clinical improvement might be observed even in absence of detectable increase of protective antibody levels and this has resulted in best practice statement from the UK (http://www.rcpch. ac.uk/sites/default/files/asset_library/Publications/I/Immunocomp.pdf; accessed June 2014) and uncertainties together with the growing neglect of societal adherence to routine immunizations has prompted the Medical Advisory Committee of the Immune Deficiency Foundation (US) to issue recommendations based on published literature and the collective experience of the committee members (83). The prophylactic vaccination of household members of these patients groups is highly recommended.…”
Section: Vaccination and Pidmentioning
confidence: 99%